Multi-objective optimization of building-integrated microalgae photobioreactors for energy and daylighting performance. (October 2021) - Talaei, Maryam; Mahdavinejad, Mohammadjavad; Azari, Rahman; Prieto, Alejandro; Sangin, Hamed
Abstract: As a state-of-the-art green façade technology, building-integrated microalgae bioreactor has the potential to reduce buildings' carbon footprint and energy consumption. The present study aims to address the knowledge gap in the energy and daylighting performance of algae photobioreactor façade. The paper first studies the effects of algae windows on building energy saving through simulation analysis of an office building in Mashhad, Iran, with a cold semi-arid climate. It also presents a multi-objective optimization framework for the optimization of the energy and daylighting performance of algae windows integrated with an office building facade. Two optimization metrics include maximum Useful Daylight Illuminance (UDI) (%), and minimum Energy Use Intensity (EUI) (kWh/m 2 /yr), representing optimal daylighting and energy performance metrics, respectively. The results demonstrate that a microalgae window significantly reduces building energy consumption comparing with single-glazed, double-glazed, and water windows. The extent of energy savings varies with window size, algae density, and façade orientation. The proposed optimization framework helps increase the average values of energy performance metrics by 21.37%, 33.25%, 36.22%, 39.67%, and daylighting metrics by 4.60%, 14.43%, 13.34%, 14.33%, in the north, south, east, and west, respectively and sequentially. Sensitivity analysis demonstrates that window size has the highest effect on two studied performance metrics for all orientations, while algae density has minimal effect on energy consumption and no considerable effect on daylighting performance. Building energy performance simulation is validated by ASHRAE140-2017. Highlights: A multi-objective optimization approach is proposed to support the building-integrated microalgae bioreactor design. Energy performance of microalgae façade window is compared in BSk and Csa climate zones. Microalgae bioreactor window is optimized for energy and daylighting performance. The highest average EUI and UDI values increased by 39.67% and 4.60% in the west and south, respectively. Energy performance in Honeybee Plugin is validated with ASHRAE 140–2017.